Chemical Composition Analysis of the Patented Naoxueshuan Formula Based on UPLC-Q-TOF MS and GC-MS - Chang LIU; Hui-qin WU; Jiang-bo QI; Hong-ling LIANG; Zhi-hua LIU; Hua-qiang HUANG; Su-ming YANG; Xi ZHOU; Fang HUANG; Hui-tai LUO (Zhipu Xuebao)
The Patented Naoxueshuan formula is an empirical formula for treating cerebral thrombosis, which has been proven to have significant and stable therapeutic effects through long-term clinical application. The Naoxueshuan formula has rich chemical components and diverse structures. In this study, chemical compositions of the Patent Naoxueshuan formula were analyzed by using ultra-performance liquid chromatography-time of flight mass spectrometry (UPLC-Q-TOF MS) and gas chromatography-mass spectrometry (GC-MS). For UPLC-Q-TOF MS analysis, the decoction of Naoxueshuan formula was separated using a Waters BEH C18 column (100 mm×2.1 mm, 1.7 μm). The mobile phase was comprised of 0.1% formic acid solution and acetonitrile with the flow rate of 0.3 mL/min. MS data was collected under positive and negative ion modes. For GC-MS analysis, the Agilent DB-5MS capillary column (30 m×0.25 mm, 0.25 μm) was employed to analyze the volatile components of the decoction of Naoxueshuan formula. The GC-MS analysis was performed under programmed heating conditions with electron ionization (EI) as the ion source and a scanning mass range of m/z 50-550. The main chromatographic peaks in both liquid and gas chromatograms were identified and analyzed according to the secondary mass spectrum information, NIST standard spectrum library and literatures. A total of 61 non-volatile components are identified in the Naoxueshuan decoction, including 14 flavonoids, 13 terpenoids, 9 glycosides, 5 organic acids, and 10 other types of compounds. A total of 29 volatile components are identified in the Naoxueshuan decoction, including 17 hydrocarbons, 3 alcohols, 1 aldehydes, 1 esters, 3 phenols, 2 terpenes and 2 other types of compounds. Among them, the organic acids are mainly from Salvia miltiorrhiza Bunge, the flavonoids are mainly from Pueraria lobata, Astragalus membranaceus (Fisch.) Bunge and Carthamus tinctorius L., the terpenoids are mainly from Salvia miltiorrhiza Bunge and Cornus officinalis Sieb. et Zucc. The volatile components are mainly from Ligusticum sinense, Fructus Amomi, Alpinia katsumadai Hayata, and Semen Alpiniae Katsumadai. This study provides an effective and comprehensive method for qualitative analysis of the chemical components in the Patented Naoxueshuan formula, and also provides data support for clarifying effective substances and establishing a quality evaluation system.